2007
DOI: 10.1002/bies.20664
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge‐making distinctions in synthetic biology

Abstract: SummarySynthetic biology is an increasingly high-profile area of research that can be understood as encompassing three broad approaches towards the synthesis of living systems: DNA-based device construction, genome-driven cell engineering and protocell creation. Each approach is characterized by different aims, methods and constructs, in addition to a range of positions on intellectual property and regulatory regimes. We identify subtle but important differences between the schools in relation to their treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
94
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 161 publications
(101 citation statements)
references
References 70 publications
0
94
0
2
Order By: Relevance
“…It is similar to protocell creation (O'Malley et al 2008) in seeking to understand the process of evolution, biological organization, and the nature of modularity and evolvability.…”
Section: Is Semisynthetic Evolvability Still Evolvability?mentioning
confidence: 99%
“…It is similar to protocell creation (O'Malley et al 2008) in seeking to understand the process of evolution, biological organization, and the nature of modularity and evolvability.…”
Section: Is Semisynthetic Evolvability Still Evolvability?mentioning
confidence: 99%
“…In a previous literature-based study, one of us identified three types of synthetic biology: DNA-based device construction, genome-driven cell engineering, and protocell creation (see O'Malley et al, 2008). Those involved in the first type of work seek to develop component parts in order to assemble ever-larger devices and systems.…”
Section: Epistemics Constructors and Engineersmentioning
confidence: 99%
“…Modern synthetic biology consists of three broad approaches of DNA-based device construction, genome-driven cell engineering and protocell creation (O'Malley et al 2007). It "aims to design and engineer biologically based parts, novel devices and systems as well as redesigning existing, natural biological systems" (Royal Academy of Engineering 2009, p. 6).…”
Section: Introductionmentioning
confidence: 99%